1993
DOI: 10.1071/pp9930231
|View full text |Cite
|
Sign up to set email alerts
|

Time of Flowering Affects Grain Quality and Spikelet Partitioning Within the Rice Panicle

Abstract: Anthesis of spikelets in the panicle of a tall indica rice cultivar, Kajalghara, was completed within a period of 7 days. Development progressed in basipetal fashion from the spikelets of the uppermost primary branch of the panicle to the lowermost. According to the timing of onset of anthesis, spikelets of the panicle were segregated into seven groups. Dry mass accumulation and starch and assimilate (soluble carbohydrates and amino acids) contents of each group were studied from anthesis to grain maturity. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 0 publications
5
93
0
2
Order By: Relevance
“…This result showed that split application of nitrogen fertilizer at panicle initiation growth stage decreases number of un-filled spikelet's per panicle as compared to the control treatment. This result is in agreement with findings of many authors (Mohapatra et al, 1993;Yang et al, 2006). Time of nitrogen fertilizer application statistically influenced total dry biomass (P<0.001) ( Table 2).…”
Section: Resultssupporting
confidence: 83%
“…This result showed that split application of nitrogen fertilizer at panicle initiation growth stage decreases number of un-filled spikelet's per panicle as compared to the control treatment. This result is in agreement with findings of many authors (Mohapatra et al, 1993;Yang et al, 2006). Time of nitrogen fertilizer application statistically influenced total dry biomass (P<0.001) ( Table 2).…”
Section: Resultssupporting
confidence: 83%
“…In general, earlier-flowering superior spikelets, usually located on apical primary branches, have fast-filling and heavier grains. Later-flowering inferior spikelets, on the other hand, are usually located on proximal secondary branches, and are either sterile or have poor and slow-filling grains that are unsuitable for human consumption [32,33] . The problem of slow-filling grain in inferior spikelets is even worse in newly bred super rice cultivars, although they generally show a yield potential of 8%-20% more than other rice cultivars [28,34] .…”
Section: Improving Grain Fill In Later-flowering Inferior Spikeletsmentioning
confidence: 99%
“…In addition, the rate of the grain-filling process after anthesis was evaluated as another parameter of the effi ciency of grain fi lling, because it should be related directly to the transport of photosynthates. The position of the spikelets examined in a panicle was also taken into account, as the effi ciency of grain fi lling is strongly dependent on the spikelet position in a panicle (Mohapatra et al, 1993;Ishimaru et al, 2003).…”
mentioning
confidence: 99%